2019
DOI: 10.21203/rs.2.13657/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linked candidate genes of different functions for white mold resistance in common bean (Phaseolus vulgaris. L) are identified by QTL-based pooled sequencing

Abstract: Background White mold (WM) is a major disease in common bean ( Phaseolus vulgaris L.), and its complex quantitative genetic control has limited the development of WM resistant cultivars. WM2.2 is one of the nine meta-QTL that has a major effect on WM tolerance. This QTL explains up to 35% of the phenotypic variation and was previously mapped to a large interval on Pv02. Our objective was to narrow the interval of this QTL using QTL-based bulk segregant analysis.Results The phenotypic and genotypic data from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have identified resistant genes GmGST of glutathione transferase and GmCH1 of chitinase via cloning, which increase resistance to S. sclerotiorum in soybean [155,156]. Similarly, the silencing of the endo-polygalacturonase gene (SsPG1), cellobiohydrolase gene (SsCBH), and oxaloacetate acetylhydrolase gene (SsOAH1) in B. napus led to a reduction in disease by 40%, showing the path in managing the disease via host-induced gene silencing [157]. In common bean, genomic regions WM2.2a and WM2.2b are linked to playing a role in resistance, of which the latter triggers physiological resistance and the former with avoidance mechanisms [158].…”
Section: Genetic Improvement Of Host Resistance To S Sclerotiorummentioning
confidence: 99%
“…Recent studies have identified resistant genes GmGST of glutathione transferase and GmCH1 of chitinase via cloning, which increase resistance to S. sclerotiorum in soybean [155,156]. Similarly, the silencing of the endo-polygalacturonase gene (SsPG1), cellobiohydrolase gene (SsCBH), and oxaloacetate acetylhydrolase gene (SsOAH1) in B. napus led to a reduction in disease by 40%, showing the path in managing the disease via host-induced gene silencing [157]. In common bean, genomic regions WM2.2a and WM2.2b are linked to playing a role in resistance, of which the latter triggers physiological resistance and the former with avoidance mechanisms [158].…”
Section: Genetic Improvement Of Host Resistance To S Sclerotiorummentioning
confidence: 99%